Customers Preference Attributes in the Usage of Core Banking Services: An Empirical Investigation - Giddaiah, Repalle; Karamala, Padmasree (International Journal of Social Sciences and Management, 2014)
Core banking services are increasingly becoming popular because of convenience and flexibility. The study was undertaken all the banking customers of Nandyal town. The sample size of the study was 250. The present study is based on the primary as well secondary data. The primary data is collected from the bank customers who are residing in Nandyal town. Data is analyzed and presented in tables. Statistical tools like percentages and weighted average method were used with the help of SPSS packages. The paper examines to know the customer preference attributes in the usage of core banking services and factors affected them in using core banking services. The finding of the study is majority of the customer’s are preference is given by attributes convenience, availability of places, safety and security and familiarity of services followed by attributes cost of transactions, reliability, availability of time and accessibility of services. The study is useful to the corporate world to tap this area and improve the e-service standards of the banking sector. DOI: http://dx.doi.org/10.3126/ijssm.v1i3.10586 Int. J. Soc. Sci. Manage. Vol.1(3) 2014: 108-112